2002
DOI: 10.1097/00004714-200212000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Efficacy of Naltrexone in the Prevention of Alcohol Relapse: Results From a German Multicenter Study

Abstract: In a placebo-controlled, double-blind German multicenter study (seven sites) the efficacy of naltrexone as an adjunctive treatment in alcoholism to maintain abstinence was assessed for 12 weeks. A total of 171 detoxified patients (97.7% met the DSM-III-R criteria for alcohol dependence) were included. Patients had been abstinent for a mean of 19.5 +/- 9.4 days at study entry. Eighty-four and 87 patients were randomized to receive naltrexone (50 mg/day) and placebo, respectively. Each site was instructed to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(76 citation statements)
references
References 36 publications
4
66
0
6
Order By: Relevance
“…The current guidelines for the pharmacotherapy of alcohol dependence with opioid antagonist recommends daily use of naltrexone alongside nonpharmacological interventions (Balldin et al, 2003;O'Malley et al, 2003;O'Malley, 1995;Srisurapanont and Jarusuraisin, 2002). However, the treatment regimen has failed to reduce alcohol drinking in several studies (Gastpar et al, 2002;Krystal et al, 2001) and patients treated with naltrexone have experienced adverse effects that have led to poor medication compliance and impaired treatment outcome (Kranzler et al, 2000;Oncken et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The current guidelines for the pharmacotherapy of alcohol dependence with opioid antagonist recommends daily use of naltrexone alongside nonpharmacological interventions (Balldin et al, 2003;O'Malley et al, 2003;O'Malley, 1995;Srisurapanont and Jarusuraisin, 2002). However, the treatment regimen has failed to reduce alcohol drinking in several studies (Gastpar et al, 2002;Krystal et al, 2001) and patients treated with naltrexone have experienced adverse effects that have led to poor medication compliance and impaired treatment outcome (Kranzler et al, 2000;Oncken et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the results of eleven controlled studies with a total of about 1,500 patients have been published [18][19][20][21][22][23][24][25][26][27][28] . With the exception of three trials [24,27,28] , results revealed a superiority of naltrexone to placebo. Patients receiving naltrexone were less likely to relapse to heavy drinking and had fewer drinking days.…”
mentioning
confidence: 99%
“…In line with these last data, the subsequent multicenter study by Gastpar et al [21] also confi rmed the safety but not the effi cacy of naltrexone in alcohol relapse prevention.…”
Section: Anti-craving Drugsmentioning
confidence: 65%